Fascinating stories of forgotten lives : rediscovering some Old Testament characters - Swindoll, Charles R. (Nashville : W Pub. Group, 2005)
"Portrait of twelve lives from the Old Testament whose lives have great lessons to teach us"--Provided by publisher.
Often-overlooked lives of significance -- Cain : the farmer who murdered his brother -- Abraham : the father who released his son -- Esau : the son who couldn't win -- Achan : the man whose sin brought calamity -- Samuel : the boy who heard God's voice -- Saul : the king who refused to bow -- Abigail : the woman who saved her husband's neck -- Absalom : the rebel Prince Charming -- Rehoboam : the reckless phony -- Jabez : the unknown who became well known -- Naaman : the officer whose leprosy was cleansed -- Gehazi : the servant who got greedy -- Uzziah : the leader who became a loser.
Includes bibliographical references (pages 249-251).
Keywords: Bible -- Biography; Christian life